Cadar sebagai pilihan dalam Berpakaian pada Mahasiswi Fib Uho - Basri Hamisi; La Janu (JURNAL KABANTI: Kerabat Antropologi, 2022)
This study aims to find out and describe the reasons why FIB UHO students use the veil and how to deal with negative stigma when in a public environment, how to choose the type of vehicle, and how to adapt in the learning process. The results showed that there were three main factors that became the main reason for female students to use the veil, namely the veil as an identity of goodness, the organizational doctrine adopted, and environmental factors. The ways in which veiled students overcome obstacles are divided into several points, including how to deal with negative stigma, how to choose the type of vehicle when traveling and how to adapt to the campus environment. Overcoming negative stigma is done by displaying good behavior, being patient, showing achievements, giving explanations and removing the veil while in the family environment in the village. The methods used in choosing the type of vehicle when traveling are renting an ojek with a female driver, asking family or relatives to take them, using public transportation (pete-pete) when there are female passengers and walking if this is not possible. Use public transportation. To adapt to the campus environment, the way to do it is to choose a front seat so that later when given the opportunity to speak, the voice of a veiled woman can be heard clearly.